Distinct functional roles of primate grasping hands and feet during arboreal quadrupedal locomotion. Issue 88 (November 2015) - Patel, Biren A.; Wallace, Ian J.; Boyer, Doug M.; Granatosky, Michael C.; Larson, Susan G.; Stern, Jack T.
Abstract: It has long been thought that quadrupedal primates successfully occupy arboreal environments, in part, by relying on their grasping feet to control balance and propulsion, which frees their hands to test unstable branches and forage. If this interlimb decoupling of function is real, there should be discernible differences in forelimb versus hind limb musculoskeletal control, specifically in how manual and pedal digital flexor muscles are recruited to grasp during arboreal locomotion. New electromyography data from extrinsic flexor muscles in red ruffed lemurs ( Varecia rubra ) walking on a simulated arboreal substrate reveal that toe flexors are activated at relatively higher levels and for longer durations than finger flexors during stance phase. This demonstrates that the extremities of primates indeed have different functional roles during arboreal locomotion, with the feet emphasizing maintenance of secure grips. When this dichotomous muscle activity pattern between the forelimbs and hind limbs is coupled with other features of primate quadrupedal locomotion, including greater hind limb weight support and the use of diagonal-sequence footfall patterns, a complex suite of biomechanical characters emerges in primates that allow for the co-option of hands toward non-locomotor roles. Early selection for limb functional differentiation in primates probably aided the evolution of fine manipulation capabilities in the hands of bipedal humans.